Deep learning in the field of disease diagnosis - S. Harish Kumar, K; Micheal Jerald, Dijo; Emmanuel, A (International Journal of Engineering and Technology, 2018)
A good treatment is dependent on the accuracy of the diagnosis. The cure for the disease starts with the process of diagnosis. All these years, the grade and standard of the medical field has been increasing exponentially, yet there has been no significant downfall in the rate of unintentional medical errors. These errors can be avoided using Deep learning algorithm to predict the disease. The Deep Learning algorithm scans analyses and compares the patient's report with its dataset and predicts the nature and severity of the disease. The test results from the patientâ€™s report are extracted by using PDF processing. More the medical reports analyzed, more will be the intelligence gained by the algorithm. This will be of great assistance to the doctors as they can interpret their diagnosis with the results predicted by the algorithm.Â Â